Redescription of six feather mite species of the genus Proterothrix Gaud, 1968 (Analgoidea: Proctophyllodidae: Pterodectinae) from the “Édouard Louis Trouessart” Collection - Constantinescu, Ioana Cristina; Chișamera, Gabriel Bogdan; Adam, Costică (Zootaxa, 2018)
Six feather mite species presently referred to the genus Proterothrix Gaud, 1968 (Proctophyllodidae: Pterodectinae) were briefly described without being drawn by a French zoologist Édouard Louis Trouessart in the end of the 19th century. The type material used for description of these species is still preserved in the Muséum National d’Histoire Naturelle (Paris, France). Based on this material, we provide detailed redescriptions, according to the modern format used for pterodectine mites, for the following species: Proterothrix diminuta (Trouessart, 1899), P. modesta (Trouessart, 1899), and P. phyllura (Trouessart, 1899) from Manucodia ater (Lesson) (Corvida: Paradisaeidae); P. emarginata (Trouessart, 1899) from M. chalybatus (J. R. Forster) (Corvida: Paradisaeidae); P. paradisiaca (Trouessart, 1885) from Paradisaea minor Shaw (Corvida: Paradisaeidae) and Sericulus chrysocephalus (Lewin) (Corvida: Ptilonorhynchidae); and P. xiphiura (Trouessart, 1885) from Psarisomus dalhousiae (Jameson) (Tyranni: Eurylaimidae). The lectotypes and paralectotypes have been designated herein for all examined species.